Atypical Posterior Reversible Encephalopathy Syndrome with Intraventricular Hemorrhage in a Patient with Eclampsia : A Case Report - Woo Hyeong Park; Sang Koo Lee; Young Jin Kim; Jung-Ho Yun; Jaewoo Chung; In-Ho Jung; Sung Jin Kim; Tae Woong Bae; Chun-Sung Cho (Journal of Korean Neurosurgical Society, 2026)
Posterior reversible encephalopathy syndrome (PRES) typically involves parieto-occipital regions but rarely presents with extensive central involvement and intraventricular hemorrhage (IVH). We report a rare case of atypical PRES with extensive central involvement and IVH in a patient with eclampsia, emphasizing diagnostic challenges and favorable outcomes. Initial CT showed IVH in all ventricles and bilateral basal ganglia hypodensities. Following emergency cesarean section, brain magnetic resonance imaging revealed typical parieto-occipital vasogenic edema along with atypical involvement of the pons, midbrain, bilateral basal ganglia, and thalami, consistent with a central variant of PRES. Susceptibility-weighted imaging showed microhemorrhages in the basal ganglia, while magnetic resonance venography excluded cerebral venous thrombosis. Conservative management with strict blood pressure control and seizure prophylaxis resulted in complete radiological resolution on follow-up imaging, and the patient was discharged without neurological deficits. Prompt recognition of atypical PRES patterns prevents misdiagnosis and unnecessary interventions despite severe radiological findings.